2022
DOI: 10.7554/elife.78374
|View full text |Cite
|
Sign up to set email alerts
|

Unsuppressed HIV infection impairs T cell responses to SARS-CoV-2 infection and abrogates T cell cross-recognition

Abstract: In some instances, unsuppressed HIV has been associated with severe COVID-19 disease, but the mechanisms underpinning this susceptibility are still unclear. Here, we assessed the impact of HIV infection on the quality and epitope specificity of SARS-CoV-2 T cell responses in the first wave and second wave of the COVID-19 epidemic in South Africa. Flow cytometry was used to measure T cell responses following PBMC stimulation with SARS-CoV-2 peptide pools. Culture expansion was used to determine T cell immunodom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 59 publications
3
22
0
Order By: Relevance
“…Although PLWH represent a particularly vulnerable patient population, the impact of T cell-mediated immunity in case of SARS-CoV-2 infection has not been fully elucidated in this cohort. Early results indicate impaired frequencies of SARS-CoV-2-specific CD4+ T cells producing IFN-γ and TNF-α in patients with unsuppressed HIV infection, compared to PLWH with controlled viremia ( Figure 3 B) [ 30 ]. However, no significant differences on the CD8+ T cell level were identified [ 30 ].…”
Section: Sars-cov-2-specific T Cells In People Living With Hiv (Plwh)mentioning
confidence: 99%
See 4 more Smart Citations
“…Although PLWH represent a particularly vulnerable patient population, the impact of T cell-mediated immunity in case of SARS-CoV-2 infection has not been fully elucidated in this cohort. Early results indicate impaired frequencies of SARS-CoV-2-specific CD4+ T cells producing IFN-γ and TNF-α in patients with unsuppressed HIV infection, compared to PLWH with controlled viremia ( Figure 3 B) [ 30 ]. However, no significant differences on the CD8+ T cell level were identified [ 30 ].…”
Section: Sars-cov-2-specific T Cells In People Living With Hiv (Plwh)mentioning
confidence: 99%
“…Early results indicate impaired frequencies of SARS-CoV-2-specific CD4+ T cells producing IFN-γ and TNF-α in patients with unsuppressed HIV infection, compared to PLWH with controlled viremia ( Figure 3 B) [ 30 ]. However, no significant differences on the CD8+ T cell level were identified [ 30 ]. Moreover, Adachi et al observed a transient decrease in CD4+ T cell, CD8+ T cell, and total lymphocyte counts during SARS-CoV-2 infection [ 114 ].…”
Section: Sars-cov-2-specific T Cells In People Living With Hiv (Plwh)mentioning
confidence: 99%
See 3 more Smart Citations